Numerical Study Of Mixed Convection Boundary Layer Flow Near The Lower Stagnation Point Of A Horizontal Circular Cylinder In Nanofluids - Norhafizah, Md Sarif; Mohd Zuki, Salleh; Abdul Rahman, Mohd Kasim; Leony, Tham; Roslinda, Nazar (Asian Research Publishing Network (ARPN), 2016)
The steady mixed convection boundary layer flow over a horizontal circular cylinder filled with nanofluids has been investigated numerically using different types of nanoparticles. These nanoparticles presences in the fluids increase the thermal conductivity up to approximately two times and thus enhancing the performance of the heat transfer. Enhancement of heat transfer is essential subject from an energy saving perspective, therefore the past years has witnessed extensive research on the convective heat transfer in nanofluids. In this paper, the nanofluid model proposed by Tiwari and Das has been used as this model is successfully applied in several papers. The problem is then being extended for the case of convective boundary conditions where the bottom surface of the cylinder is heated by convection from hot fluids. The resulting partial differential equations are solved numerically using implicit finite-difference scheme via Keller-box method. The effects of mixed convection  , nanoparticle volume fraction,  and conjugate parameters  on the temperature and velocity profiles near the lower stagnation point of the cylinder x  0 are examined. Detailed results are presented through figures for the temperature and velocity profiles. It is found that as the conjugate  and mixed convection parameter  increase, the temperature and velocity profile increases, while an increase in the nanoparticle volume fraction  led to the increment of temperature profile and velocity profiles at   1.